Etika Lingkungan Dan Implementasinya Dalam Pemeliharaan Lingkungan Alam Pada Masyarakat Kampung Naga - Citra Nurkamilah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2018)
The environmental damage is the reflection of the disruption of the lungs of the earth (forest) result of the attitude of the human antroposentrik the exploit is excessive. To balance the natural environment so it will not be damaged is the regained human behavior or ethics that will save the environment. This ethic has been long applied in Kampung Naga which they have  the alternative view of life  regarding the human relation with the environment that considered sacred. The purpose of this research is to know about the environmental ethics in Kampung Naga in protecting their environment. This research uses descriptive qualitative method with anthropological and phenomenological approaches. The result of this research is every people in Kampung Naga has the environmental ethic that is quite intent by referring to values which formulated systematically based on inheritance ancestors, tangible inheritance and intangible inheritance. This has an impact of disaster mitigation (the efforts to reduce the risk) in Kampung Naga such as preventing landslides and floods, the maintenance of the integrity of the environment, the maintenance of the forest as the lungs of life,  and every ecological creatures in that region also obeyed the ethic which presented by ekosentrisme and deep ecology. So, the environmental ethic in Kampung Naga shows about the balance of the ecological relation